Pharmacological and molecular analysis of the effects of Huangqi Jianzhong decoction on proliferation and apoptosis in GES-1 cells infected with H. pylori - Hu, Jingnan; He, Tao; Liu, Jianfang; Jia, Sujie; Li, Bolin; Xu, Weichao; Liao, Man; Guo, Lifang (Frontiers in Pharmacology, 2022)
Current anti-H.pylori treatment can cause antibiotic resistance and other adverse reactions. Huangqi Jianzhong Decoction (HQJZD), is a prescription form of traditional Chinese medicine for chronic gastritis that increases probiotics and inhibits H.pylori. Thus, its anti-bacterial activity was used for preliminary evaluation against H.pylori, and a pharmacology analysis was performed to predict its underlying mechanisms. Methods: Human GES-1 cells were divided into blank control group, model group, HQJZD low-dose (2.08 mg·mL-1) and high-dose groups (4.16 mg·mL-1), and positive control group (amoxicillin, 5 μg·mL-1). After culture, the CCK-8 method was used to detect cell viability, flow cytometry was used to detect cell apoptosis rate, and RT-qPCR was used to detect the expression of virulence factors mRNA, including HpPrtC, OPiA, IceA1, and BabA2. Based on the anti-H.pylori infection effect, network pharmacology analysis, and molecular docking technology were performed to explore the mechanisms of HQJZD in treating H.pylori gastritis. Results: We noted lower cell survival rates in the model group but higher apoptosis rates and mRNA expressions of HpPrtC, OPiA, IceA1, and BabA2 than in the control group (P<0.05). Compared to the model group, the cell survival rate of each dosage group of Huangqi Jianzhong Decoction and the positive control group significantly increased, and the apoptosis rate and the mRNA expressions of HpPrtC, OPiA, IceA1, and BabA2 were significantly decreased, and the effect in each dose of HQJZD group was dose-dependent (P<0.05). Through network pharmacological analysis, 6 key active components of HQJZD and 102 potential target proteins for the treatment of H.pylori-related gastritis were screened, involving 159 signaling pathways. The molecular docking results revealed that the 6 active compounds had a strong binding ability to the target proteins of ALB, IL6, AKT1, IL1B, and JUN. Conclusion: HQJZD effectively increases the proliferation rate of human GES-1 cells after infection while reducing the level of apoptosis. The mechanism may be related to multiple components, multiple targets and pathways, which provides a scientific basis for further elucidating the mechanism of action, pharmacodynamic material basis, and clinical application of HQJZD against H.pylori infection.